MEDIA PEMBELAJARAN PREZI DALAM MENINGKATKAN KEMAMPUAN PENGUASAAN KONSEP SISWA MATA PELAJARAN BAHASA INGGRIS KELAS XII TKJ SMK NEGERI 6 TAKALAR - Sunarti Rasdin; Mudeing Jais; Nurdin (STKIP Subang, 2024)
The main problem in this study is how to apply prezi learning media to see the ability to master the concepts of English subjects in TKJ students of SMK Negeri 6 Takalar. This study aims to find out the ability to master the concept of English subject XII TKJ students of SMK Negeri 6 Takalar by using learning media, namely prezi. This type of research is quantitative research that has tests, namely the initial test (pre-test) and the final test (post-test). The research procedure includes preparation, implementation, and conclusion. The sample of this study was class XII TKJ SMK Negeri 6 Takalar as many as 62 students. The results showed that in the initial test (pretest) the average student was 36.04 with a very low category. Classically, it has not met the KKM set by the school which is 75, individually from 62 students only 1 student is complete. While in the final test (pretest) the average student was 83.38 with a high category and individually from 62 students only 4 students were not complete, as many as 58 students were complete. From the results of the final test it was found that there was an increase of 47.34% from the initial test. Based on the results of the study above, it can be concluded that the ability to master English concepts of XII TKJ class students at SMK Negeri 6 Takalar Takalar Regency through the use of prezi learning media has increased.